Cultivation of previously uncultured sponge-associated bacteria using advanced cultivation techniques: A perspective on possible key mechanisms - Jung, Dawoon; Machida, Koshi; Nakao, Yoichi; Owen, Jeffrey S.; He, Shan; Kindaichi, Tomonori; Ohashi, Akiyoshi; Aoi, Yoshiteru (Frontiers in Marine Science, 2022)
Most of the microbes from natural habitats cannot be cultivated with standard cultivation in laboratory, and sponge-associated microbes are no exception. We used two advanced methods based on a continuous-flow bioreactor (CF) and in situ cultivation (I-tip) to isolate previously uncultivated marine sponge-associated bacteria. We also characterized the physiological properties of the isolates from each method and attempted to clarify the mechanisms operating in each cultivation method. A greater number of novel bacteria were isolated using CF and in situ cultivation compared to standard direct plating (SDP) cultivation. Most isolates from CF cultivation were poor growers (with lower specific growth rates and saturated cell densities than those of isolates from SDP cultivation), demonstrating that it is effective to carry out pre-enrichment cultivation targeting bacteria that are less competitive on conventional cultivation, especially K-strategists and bacterial types inhibited by their own growth. Isolates from in situ cultivation showed a positive influence on cell recovery stimulated by chemical compounds in the extract of sponge tissue, indicating that some of the bacteria require a “growth initiation factor” that is present in the natural environment. Each advanced cultivation method has its own distinct key mechanisms allowing cultivation of physiologically and phylogenetically different fastidious bacteria for cultivation compared with conventional methods.